Investigation of the Evaporation Process of a Freely Falling Droplet in Turbulent Channel Flow - Mohammadi, Elham (Curtin University, 2020)
The present work serves to understand complicated mechanisms associated with dilute region of a spray and investigate the effect of turbulent Reynolds number on the evaporation by developing a CFD code and simulating a single droplet freely falling in a fully developed turbulent channel flow. It is revealed that turbulence has significant effect on the evaporation of the droplet in channel flow though higher turbulent Reynolds number does not necessarily increase the evaporation.